Game on : tempting twenty-eight - Evanovich, Janet (New York : Atria Books, 2021)
Stephanie and fellow apprehension agent, Diesel, are on the trail of the same fugitive: Oswald Wednesday, an international computer hacker as brilliant as he is ruthless. Unsure if Diesel is her partner or her competition in this case, she'll need to watch her back every step of the way as she sets the stage to draw Wednesday out from behind his computer and into the real world.
Includes a sneak peak of The Recovery Agent by Janet Evanovich.
Keywords: Plum, Stephanie -- (Fictitious character) -- Fiction; Bounty hunters -- Fiction; Women bounty hunters -- Fiction; Hackers -- Fiction; Bail bond agents -- New Jersey -- Fiction; Trenton (N.J.) -- Fiction; Detective and mystery fiction; Humorous fiction